PENINGKATAN KAPASITAS PENGELOLA BUMDesa MELALUI PELATIHAN DAN PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN : Improving the Capacity of BUMDesa Managers through Training and Assistance in Financial Reporting - Raharjo, Taufik; Rahayu, Kusumawati; Roby Syaiful, Ubed (Jurnal Abdi Masyarakat Indonesia (JAMIN), 2024)
This community service activity (PkM) aims to assist partners in preparing accurate and compliant financial reports through training and mentoring for Village-Owned Enterprises (BUMDesa) managers in Pandeglang Regency, especially in Cadasari, Mekarjaya, and Koroncong Districts. The background to this community service is that many BUMDesa still do not have good and correct financial reports. The reports that can be made by BUMDesa are still limited to cash inflow and cash outflow books. This community service is carried out in three stages: planning, implementation, and evaluation. At the planning stage, a Focus Group Discussion (FGD) was held with the Pandeglang Regency DPMD, which resulted in the concept of training and mentoring for preparing BUMDesa financial reports. The implementation stage went well, although there were still some obstacles. At the evaluation stage, an analysis of the emerging problems was carried out, and recommendations were given for improvement in similar activities in the future. The results achieved from this activity were bookkeeping in the form of profit and loss reports, balance sheets, financial position reports, and BUMDesa health reports